KUALITAS MIE BASAH DENGAN PENAMBAHAN TEPUNG UBI TALAS - Ngakan Putu Sudiarta (JURNAL GASTRONOMI INDONESIA, 2022)
This study used qualitative descriptive analysis methodologies for data analysis in order to determine and describe how the organoleptic test findings of wet noodles using taro sweet potato flour were perceived in terms of flavor, color, scent, and texture. Studying societal issues, societal practices, and events, including how attitudes, worldviews, and current processes interact with the influence of phenomena. Wet oodles with the inclusion of taro tuber flour are known to have very good ratings in terms of taste (80%), texture (85%), and overall perception (80%) based on the findings of experiments, organoleptic tests by panelists, and continued with Likert scale analysis.